Konflik-konflik Sosial Agama dan Strategi Penyelesaiannya pada Masyarakat Islam dan Kristen di Desa Tembung, Kecamatan Percut Sei Tuan, Kabupaten Deli Serdang - Hasibuan, Nur Sakinah; Daulay, Maraimbang; Siregar, Husna Sari (Lembaga Yasin AlSys, 2023)
This study aims to find out how the social religious conflict between Islam and Christianity in Tembung and how they overcome the conflict, especially in the resolution strategy. This study uses a qualitative method, which is a study conducted by collecting data by examining locations where there are social conflicts and religions being studied to find out facts that exist in society. This study uses the Sociology of Religion approach method. The sociology of religion approach is an approach that talks about one of the social phenomena, namely religion as a social manifestation. The results of this study show that religious social conflicts in Tembung are due to the establishment of pig pens, pets such as dogs that roam around and the lack of peace caused by the establishment of palm wine stalls there. The problem was resolved by the village government and residents of Tembung village. The problem solving stage has been said to be running smoothly by means of socialization and giving warnings to those who have conflicts.